2007
DOI: 10.1007/s11575-007-0044-y
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, competition and regulatory change: Assessing interrelationships at the industry level

Abstract: and Key Results■ This paper focuses on the overall themes of the issue to examine the interrelationships between innovation, competition and regulatory change in international business.■ It provides a synthesis by highlighting recent interlinked developments in two contrasting industries dominated by large multinationals -pharmaceuticals and automotives, with specific reference to cars.■ This industry based assessment highlights the technical, economic and regulatory forces that have together changed the busin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…IP rules, for both protection and access, are both a cause and a result of economic activity: it is hard to tell when changes in markets for goods and services affect IP policies and practices and when changes in IP policies and practices affect markets for goods and services. Growth in economic development and IP protections have been uneven, varying not just by region (developed versus developing parts of the world), but also by industrial sector, and are found especially among knowledge intensive industries such as genomics and digital technology, and in places hospitable to them, such as Singapore (Baber, ; Fai & Morgan, ), and Silicon Valley. Arguments for IP access , on the other hand, are more in evidence in regions and communities where basic knowledge via schooling is most in demand and least in evidence.…”
Section: Background: Higher Education and Intellectual Property In A mentioning
confidence: 99%
“…IP rules, for both protection and access, are both a cause and a result of economic activity: it is hard to tell when changes in markets for goods and services affect IP policies and practices and when changes in IP policies and practices affect markets for goods and services. Growth in economic development and IP protections have been uneven, varying not just by region (developed versus developing parts of the world), but also by industrial sector, and are found especially among knowledge intensive industries such as genomics and digital technology, and in places hospitable to them, such as Singapore (Baber, ; Fai & Morgan, ), and Silicon Valley. Arguments for IP access , on the other hand, are more in evidence in regions and communities where basic knowledge via schooling is most in demand and least in evidence.…”
Section: Background: Higher Education and Intellectual Property In A mentioning
confidence: 99%
“…The application of emission standard technologies seemed to have minor effect on the average sale of cars. Fai and Morgan (2007) examined the relationships among competition, innovation and change in regulation in business environment at international level. These factors have strong impact on automobile industry and can lead to give a direction for the future polices regarding this sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…12,13 The discovery and development phases mainly involve technical risks regarding the safety and effi cacy of the potential product, for example, whereas in the commercialisation phase they are related more to competition, fi nancial return and marketing. 5,6 Regulatory risk, related to patent legislation, for example, is present at each stage of the process.…”
mentioning
confidence: 99%
“…5,6 Regulatory risk, related to patent legislation, for example, is present at each stage of the process. 13 The aim during the discovery stage is to identify new promising chemical and biological properties of either previously known or newly synthesised substances.…”
mentioning
confidence: 99%